A151 WAIT TIMES FOR IBD SURGERY IN EDMONTON: 50% ARE WAITING TOO LONG. (15th March 2019) - Homenauth, R; Mocanu, V; Snelgrove, R; Wang, H; Kroeker, K
Abstract: Background: Despite advancement in medical therapy, approximately three-quarters of patients with Crohn's disease (CD) and one-third of ulcerative colitis (UC) patients will require surgery in their lifetime. In the absence of accepted standards for appropriate wait times for IBD surgery, we rely on expert opinion. In Alberta, the Adult Coding Access Targets for Surgery (ACATS) project has defined optimal waiting times (WT) surgery, including IBD-related surgery. Delayed surgery is believed to lead to poor outcomes and increased risk of postoperative complications. It is unknown whether IBD patients in Edmonton are receiving elective surgery (ES) within the defined WT. Aims: To determine the proportion of IBD patients who underwent elective surgery outside the provincially accepted wait times, overall and by type of surgery. Methods: This is a 5-year, retrospective, quality assurance study of adult patients in Edmonton who underwent elective IBD surgery (January 1, 2013 to Dec 31, 2017). Data was extracted from the Edmonton Elective OR Database using relevant procedure codes. Surgical wait time was defined as the time between the decision to perform surgery and the date of the procedure for each type of surgery. Descriptive statistics were calculated to determine the proportion of patients who had surgery outside the accepted WT; and how long after the accepted time they waited. Of note, patients who had emergency surgery were excluded from this analysis. Results: Overall, 385 surgeries were included. Half (50.9%) occurred outside predefined WT. For surgeries outside the window, 141 (71.9%) were done 50% beyond predefined WT with 111 (56.6%) occurring more than 100% beyond. Table 1 shows the #surgeries done electively by type, the average wait time, and the proportion done outside the accepted wait time. Conclusions: The average wait time for elective IBD surgery in Edmonton is longer than the provincially accepted wait times. Half of patients undergoing elective IBD surgery are waiting too long. Funding Agencies: